Mistaken for an empire a memoir in tongues - Imperial, Christine (Columbus Mad Creek Books, an imprint of The Ohio State University Press, 2023)
"Form-bending essays about ethnicity, language, family history, and national identity from a dual US/Philippines citizen"--
Keywords: Kipling, Rudyard -- 1865-1936.; Kipling, Rudyard -- 1865-1936 -- Translations into Tagalog -- History and criticism; Dual nationality -- Philippines; Dual nationality -- United States; Filipino Americans -- Biography; Filipino Americans -- Ethnic identity; Filipino American authors -- 21st century -- Biography